2005
DOI: 10.2113/gsecongeo.100.8.1547
|View full text |Cite
|
Sign up to set email alerts
|

Alteration Mineralogy and Stable Isotope Geochemistry of Paleoproterozoic Basement-Hosted Unconformity-Type Uranium Deposits in the Athabasca Basin, Canada

Abstract: Unconformity-type uranium deposits are characterized by mineralization developed along the contact between younger sandstone cover and underlying crystalline basement rocks. Mineralization may extend up to 400 m into the underlying basement rocks. Whereas sandstone-hosted unconformity-type deposits have been well studied, deposits hosted primarily in the basement have not. This study examines the deposits at Rabbit Lake, Dawn Lake, and McArthur River, in the Athabasca basin of Canada, which are hosted by the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 51 publications
7
72
0
Order By: Relevance
“…Several studies have now demonstrated that the unconformity-related U deposits are associated with long-lived basement-rooted structures that were likely active during basin-fill, sandstone diagenesis and U mineralisation Alexandre et al 2005Alexandre et al , 2009Polito et al 2005Polito et al , 2006bSouthgate et al 2006;Kyser 2007). In most cases, these structures have been reactivated several times since initial uraninite precipitation as testified by the typically young ages determined for most U deposits in Australia and Canada (Hills & Richards 1976;Gulson & Mizon 1980;Fayek & Kyser 1997;Fayek et al 2000Fayek et al , 2002Kyser et al 2000;Polito et al 2004Polito et al , 2005Alexandre et al 2005Alexandre et al , 2009. Therefore, the conclusion is that elements known to be associated with post-ore alteration may be useful in unconformity-related U exploration because they too indicate formation in a long-lived structure that was originally active when U mineralisation formed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have now demonstrated that the unconformity-related U deposits are associated with long-lived basement-rooted structures that were likely active during basin-fill, sandstone diagenesis and U mineralisation Alexandre et al 2005Alexandre et al , 2009Polito et al 2005Polito et al , 2006bSouthgate et al 2006;Kyser 2007). In most cases, these structures have been reactivated several times since initial uraninite precipitation as testified by the typically young ages determined for most U deposits in Australia and Canada (Hills & Richards 1976;Gulson & Mizon 1980;Fayek & Kyser 1997;Fayek et al 2000Fayek et al , 2002Kyser et al 2000;Polito et al 2004Polito et al , 2005Alexandre et al 2005Alexandre et al , 2009. Therefore, the conclusion is that elements known to be associated with post-ore alteration may be useful in unconformity-related U exploration because they too indicate formation in a long-lived structure that was originally active when U mineralisation formed.…”
Section: Discussionmentioning
confidence: 99%
“…Petrographic analysis demonstrates that sericite alteration of feldspar occurs first and furthest from the ore zone (Figure 5a), followed by sericite replacement of amphibole and sillimanite and then by increasing amounts of chlorite toward mineralisation ( Figure 5b; Polito et al 2004Polito et al , 2005. Alexandre et al (2005) demonstrated that the formation of crystalline illite/sericite from amphibole and feldspar around the U deposits in the Athabasca Basin created void space due to the minerals' contrasting molar volume. These authors proposed that void space creation promoted additional fluid flow into the basement, with the release of Mg and Fe from minerals such as amphibole, resulting in the precipitation of void-consuming chlorite.…”
Section: Syn-ore Processes In the Large Basement-hosted Uranium Deposmentioning
confidence: 99%
“…Similarly, Kotzer and Kyser (1995) concluded that the brines have a significant meteoric water component and that the high chlorinities were achieved by evaporite dissolution and reaction with feldspars. However, based on comparable isotopic analyses, Alexandre et al (2005) stated that the brines result from mixing between evaporated seawater and low-latitude meteoric waters.…”
Section: Previous Studiesmentioning
confidence: 99%
“…This difference underlines the variability of possible reductants for the formation of U deposits in sandstone basins (e.g., Kyser 2006, 2012;Yeo and Potter 2010). Ferrous iron has also been suggested as a reductant for unconformity-related U deposits in the Athabasca Basin, but its source is dominantly chlorite, a product of pre-ore clay alteration (Alexandre et al 2005). Other reductants that have been documented elsewhere include, but are not limited to, S (Beverley, South Australia; Wülser et al 2011), graphite or CO (Athabasca Basin deposits; e.g., Cuney and Kyser 2008), organic matter and H 2 S (tabular deposits, Grants U region in USA; Galloway 1980;Saucier 1980), and hydrocarbons in many types of deposits (e.g., Alexandre and Kyser 2006).…”
Section: Implications For the U Metallogeny Of The Otish Basinmentioning
confidence: 99%